1995
DOI: 10.1115/1.2822636
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Non-Darcian Forced Convection in an Asymmetrically Heated Sintered Porous Channel

Abstract: A study of non-Darcian forced convection in an asymmetric heating sintered porous channel is carried out to investigate the feasibility of using this channel as a heat sink for high-performance forced air cooling in microelectronics. A volume-averaging technique is applied to obtain the macroscopic equations with the non-Darcian effects of no-slip boundary, flow inertia, and thermal dispersion. Local non-thermal-equilibrium is assumed between the solid and the fluid phases. The analysis reveals that the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(26 citation statements)
references
References 11 publications
4
20
0
2
Order By: Relevance
“…They concluded that an optimum Darcy number exist for a porous media with a high ratio of the thermal conductivity of the solid particle to that of the fluid which can enhance the heat transfer with a smaller increase of the flow resistance. Hwang and Chao [6,7] studied convection heat transfer of air in sintered porous channels experimentally and numerically and showed that the heat transfer increased with the solid particle thermal conductivity. Jiang et al [8][9][10] studied convection heat transfer of water in non-sintered porous plate channels experimentally and numerically and showed that the packed beds greatly intensified the convection heat transfer (up to 10 times).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They concluded that an optimum Darcy number exist for a porous media with a high ratio of the thermal conductivity of the solid particle to that of the fluid which can enhance the heat transfer with a smaller increase of the flow resistance. Hwang and Chao [6,7] studied convection heat transfer of air in sintered porous channels experimentally and numerically and showed that the heat transfer increased with the solid particle thermal conductivity. Jiang et al [8][9][10] studied convection heat transfer of water in non-sintered porous plate channels experimentally and numerically and showed that the packed beds greatly intensified the convection heat transfer (up to 10 times).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, fluid flow and heat transfer in porous media has received much attention during the past five decades. Many researches have shown that porous media are an effective heat transfer augmentation technique because the porous structures intensify mixing of the fluid flow and increase the contact surface area [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The one-equation model was also used in numerical simulations. Besides, Hwang and Chao [3] and Hwang et al [4] reported heat transfer measurements for sintered copper bead porous channels, and numerically solved the two-equation model that yielded accurate predictions. They also examined the effect of the inlet thermal boundary condition on the numerical predictions.…”
Section: Introductionmentioning
confidence: 96%
“…In fact, the heat transfer coefficient is known to be dependent on various system parameters, including fluid velocity, porosity, particle geometry, and specific surface area. Consequently, a number of different empirical functions have been proposed to describe the dependence of h on these parameters (Dixon and Cresswell 1979;Amiri and Vafai 1994;Hwang et al 1995;Alazmi and Vafai 2000). While these formulations may be adequate for relatively homogeneous laboratory conditions, such idealized heat transfer coefficients cannot be expected to be applicable in naturally heterogeneous geological systems.…”
Section: Introductionmentioning
confidence: 98%